2007
DOI: 10.3759/tropics.17.87
|View full text |Cite
|
Sign up to set email alerts
|

Water utilization by local inhabitants responding to seasonal changes in water quality of river water in Central Kalimantan, Indonesia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Zuo et al (2015) reported that the pH value of water quality in the tourism development zone and the control zone was high water period > low water period > normal water period and the pH value of tourism development zone was signi cantly higher than that of control zone (p < 0.05), which coincided with the present study. Haraguchi et al (2008) reported water utilization by local inhabitants responding to seasonal changes in water quality of river water in Central Kalimantan, Indonesia. River water chemistry showed little difference between the dry season and the rainy season in the Sigi area, whereas river and canal water in the rainy season in Paduran and Pangkoh showed lower pH than in the dry season due to a high concentration of sulfuric acid in the rainy season (Haraguchi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zuo et al (2015) reported that the pH value of water quality in the tourism development zone and the control zone was high water period > low water period > normal water period and the pH value of tourism development zone was signi cantly higher than that of control zone (p < 0.05), which coincided with the present study. Haraguchi et al (2008) reported water utilization by local inhabitants responding to seasonal changes in water quality of river water in Central Kalimantan, Indonesia. River water chemistry showed little difference between the dry season and the rainy season in the Sigi area, whereas river and canal water in the rainy season in Paduran and Pangkoh showed lower pH than in the dry season due to a high concentration of sulfuric acid in the rainy season (Haraguchi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Haraguchi et al (2008) reported water utilization by local inhabitants responding to seasonal changes in water quality of river water in Central Kalimantan, Indonesia. River water chemistry showed little difference between the dry season and the rainy season in the Sigi area, whereas river and canal water in the rainy season in Paduran and Pangkoh showed lower pH than in the dry season due to a high concentration of sulfuric acid in the rainy season (Haraguchi et al 2008). Zhang et al ( 2012) exhibited spatial and temporal characteristics of hydrochemistry in typical inland river basins of middle Tianshan Mountains.…”
Section: Discussionmentioning
confidence: 99%